2023
DOI: 10.1155/2023/9049256
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mast Cell Degranulation in Atopic Dermatitis by Celastrol through Suppressing MRGPRX2

Abstract: Background. Atopic dermatitis is a common dermatological disease, and mast cell degranulation is believed to be related with the progression of atopic dermatitis. Mas-related G protein-coupled receptor-X2 (MRGPRX2), and calcium release-activated calcium channel protein 1-2 (ORAI-1, ORAI-2) are involved in mast cell degranulation. Celastrol is an active monomer of Tripterygium wilfordii, and it presents an antiatopic role. Methods. 2,4-Dinitrofluorobenzene (DNFB) and compound 48/80 (C 48/80) were used to establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Bawazir et al [79] presented C9 as a potent and, importantly, selective inhibitor of only MRGPRX2-mediated MC degranulation. Yao C et al [80] found that the improvements of AD caused by Celastrol were reversed by means of treatment with MRGPRX2 overexpression, indicating that Celastrol might affect AD via MRGPRX2. Clarithromycin already showed positive outcomes in a preliminary clinical trial in the treatment of CU.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bawazir et al [79] presented C9 as a potent and, importantly, selective inhibitor of only MRGPRX2-mediated MC degranulation. Yao C et al [80] found that the improvements of AD caused by Celastrol were reversed by means of treatment with MRGPRX2 overexpression, indicating that Celastrol might affect AD via MRGPRX2. Clarithromycin already showed positive outcomes in a preliminary clinical trial in the treatment of CU.…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds of plant origin have surfaced as MRGPRX2 inhibitory agents. Celastrol [80], for instance, has exhibited MRGPRX2 inhibition and has been shown to reduce MC production, histamine release, scratching levels, and inflammatory factor expression in mice. The inhibitory effect of Celastrol was reversed upon the overexpression of MRGPRX2 in a mouse model, supporting the notion that this effect may be mediated via MRGPRX2 rather than its orthologs [80].…”
Section: Mrgprx2 Inhibitors-potential Therapeutic Candidatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Exogenous ligands of MRGPRX2 include the cationic polymer compound 48/80 (C48/80), which is commonly used in receptor functional assays, and a variety of drugs approved by the Food and Drug Administration (FDA), such as fluoroquinolones (e.g., ciprofloxacin), neuromuscular blocking agents (e.g., rocuronium, atracurium), opioids (e.g., morphine), and many others [ 4 , 9 , 28 ]. MRGPRX2 can also be activated or inhibited by other exogenous agents, such as bacterial quorum sensing proteins, insect venoms [ 3 , 29 , 30 ], or many different plant xenobiotics ( Figure 1 ) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]; representatives of which are described in the following part of this review.…”
Section: Pathophysiological Basismentioning
confidence: 99%